24. CLINICAL, SUBCLINICAL CHARACTERISTICS AND TREATMENT RESULTS OF NEONATAL RESPIRATORY DISTRESS IN NEWBORN INFANTS AT THE NEONATAL PEDIATRIC DEPARTMENT, XANH PON GENERAL HOSPITAL, HANOI (Vietnam Journal of Community Medicine, 2025)
Objective: Describe clinical and paraclinical characteristics and treatment results of respiratory failure in newborns at the neonatal department of Xanh Pon General Hospital in 2023 - 2024.Subject and method: Study subjects: 258 medical records of neonates with respiratory distress treated at Xanh Pon General Hospital. Study design: Descriptive, retrospective data analysis.Results: In our study, the proportion of male neonates (67.4%) was higher than that of female neonates (32.6%) and was predominant in both age groups. Neonates ≤1 day old accounted for the majority (67.4%), while those >1 day old comprised 32.6%. The most common clinical sign of respiratory distress was tachypnea >60 breaths/min (79.5%), cyanosis (79.1%). Laboratory findings included leukopenia in 15.5%, anemia in 17.8%, and thrombocytopenia in 5.8% of neonates. Hypoalbuminemia was observed in 72.9%, hypoglycemia in 19.8%, and elevated CRP levels in 36%. The referral rate to higher-level hospitals was 1.9%. A high proportion of neonates with respiratory distress required respiratory support, with oxygen therapy being the most common (33.7%), followed by CPAP (22.5%) and mechanical ventilation (17.4%). All cases (100%) required antibiotic treatment.Conclusion: Respiratory distress in neonates presents with diverse clinical and paraclinical features, varying according to gestational age. The majority of affected neonates required respiratory support, yet most responded well to treatment.
Keywords: Respiratory distress; neonates; clinical features; paraclinical findings; treatment outcome.